Efficiency of Calcium Carbonate on Reducing Carbofuran Toxicity via Earthworm, Pheretima peguana (Stephenson, 1923) using Histopathological Biomarker - ปานแก้ว ประกายเพชร; ชาฮิ หรรษิตา; จิรอังกูรสกุล วรรณีย์ (YRU Journal of Science and Technology, 2019)
Currently, many insecticides are used worldwide in agriculture because they can help induce the quantity and quality of products. But they are toxic to other organisms especially humans being one of those affected. Therefore, there are laws to prohibit the use of some insecticides that are dangerous to human health. However, there are still detecting the illegal use of these insecticides. The aim of this research was analyzed the efficiency of calcium carbonate reducing carbofuran toxicity via earthworm histopathology technique. There were 4 groups by chemical type: group 1 which exposed with distilled water; group 2 which exposed with 80 mg per liter calcium carbonate group 3 which exposed with 1% carbofuran; group 4 which exposed with a mixture of 80 mg per liter calcium carbonate and 1% carbofuran (1:1). The enterocytes were appeared normal structure in group 1 and group 2. Nevertheless, they were separated from basement membrane, disorganization and hyperplasia in group 3. Moreover, the similar histopathological changes were found in group 4 in lower severity, and in some areas still found normal structure. It might be concluded that the hard water or calcium carbonate may be used to reduce the toxicity of carbofuran.